Strategi Pengembangan Atraksi Wisata Budaya di Museum Indonesia TMII sebagai Sumber Pembelajaran - Shinta Oktaviani; Meizar Rusli; Nungky Puspita (Journal of Tourism Destination and Attraction, 2015)
Indonesia, which has many resources of natural and extremely diverse culture, is a huge tourism potential. Museum was built in order to preserve those natural and cultural resources. Museum functions which are not limited only to maintenance and exhibit the collection has now expanded into one of the tourist attractions as a source of information and knowledge for tourists who visit it. As a tourist attraction, the Museum of Indonesia requires a strategy that can develop its potential as one of the leading cultural tourist attractions in TMII, moreover Indonesia. The methods used to determine the strategy in this research is SWOT analysis and figured by using SWOT Matrix and IE Matrix with the results of product development and diversification.